2020
DOI: 10.2196/14627
|View full text |Cite
|
Sign up to set email alerts
|

Media Reports as a Source for Monitoring Impact of Influenza on Hospital Care

Abstract: Background The Netherlands, like most European countries, has a robust influenza surveillance system in primary care. However, there is a lack of real-time nationally representative data on hospital admissions for complications of influenza. Anecdotal information about hospital capacity problems during influenza epidemics can, therefore, not be substantiated. Objective The aim of this study was to assess whether media reports could provide relevant info… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…A future intervention must be efficiently implemented by developing new health communication processes, considering vaccinated and nonvaccinated individual profiles defined in a periodically updated way by building, for example, specific decision trees as proposed in this research (see Figure 3 ). This must be based on improving the health communication flow on social media, in near-real time, by monitoring and adapting targeted campaigns for facing rapid information changes in the internet sphere (eg, breaking news and fake news) [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…A future intervention must be efficiently implemented by developing new health communication processes, considering vaccinated and nonvaccinated individual profiles defined in a periodically updated way by building, for example, specific decision trees as proposed in this research (see Figure 3 ). This must be based on improving the health communication flow on social media, in near-real time, by monitoring and adapting targeted campaigns for facing rapid information changes in the internet sphere (eg, breaking news and fake news) [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…This could also explain the low number of current smokers among the patients. This outbreak had an unusual male:female ratio with nine females and six males, while usually around 70% of LD patients are male [13]. However, no possible explanation could be found.…”
Section: Discussionmentioning
confidence: 80%
“…In the Netherlands, an industrial biological WWTP was identified as a common source for two clusters of LD cases in 2016 and 2017, and another iWWTP as a source for cases from 2013 to 2018 [10,11]. Since then, there have been multiple smaller clusters that were linked to WWTPs [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…There is substantial literature on forecasting, particularly for influenza [4][5][6][7][8][9][10][11]. However, forecast models are usually assessed on whether they can detect increased activity associated with outbreaks or the accuracy of daily or weekly forecasts, not the accuracy of forecasting peak activity [12].…”
Section: Introductionmentioning
confidence: 99%